Acute avulsion fractures of the pelvis in adolescent competitive athletes: prevalence, location and sports distribution of 203 cases collected - Rossi, F.; Dragoni, S. (Skeletal Radiology, 2001)
OBJECTIVE: To describe the prevalence, location and sports distribution of pelvic avulsion fractures in adolescent competitive athletes. DESIGN AND PATIENTS: One thousand two hundred and thirty-eight radiographs of the pelvis taken for focal traumatic symptoms in athletes with an age range of 11-35 years over a period of 22 years were reviewed. RESULTS: One hundred and ninety-eight adolescent athletes were affected by 203 avulsion fractures of the pelvic apophyses (five cases presented multiple locations). The localisation was the ischial tuberosity (IT) in 109 cases, anterior inferior iliac spine (AIIS) in 45 cases, anterior superior iliac spine (ASIS) in 39 cases, superior corner of pubic symphysis (SCPS) in 7 cases and iliac crest (IC) in 3 cases. Soccer (74 cases) and gymnastics (55 cases) were the sports with the highest number of avulsion fractures documented. CONCLUSIONS: Apophyseal avulsion fractures of the pelvis in adolescent competitive athletes are most common in soccer and gymnastics. The lesions are usually the consequence of sudden and forceful muscle-tendon contractions during sport activities. Plain radiographs, are determinant for the diagnosis.